Diffuse Large B-Cell Lymphoma Relapsing in Leukaemic Phase Presenting as Acute Leukaemia. Issue 12 (January 2019) - Balasubramanian, Priyavadhana; Ramteke, Prashant; Mallick, Saumyaranjan; Kumar, Lalit; Tanwar, Pranay
Diffuse large B-cell lymphoma (DLBCL) accounts for 30% to 40% of the newly diagnosed adult non-Hodgkin lymphomas, but rarely presents in leukaemic phase. Here in, we report a case of DLBCL presenting in leukaemic phase and masquerading as acute leukaemia. A 28-year-old woman presented to our outpatient department with complaints of fever for 1 week. Her peripheral blood smear showed 5% to 8% blasts. Bone marrow aspirate showed an infiltration by ~30% blasts. Flow cytometry and immunohistochemistry confirmed relapse of DLBCL. Also, patient's poor response to therapeutic regimen for DLBCL prompted to consider second differential diagnosis of acute leukaemia. This case is a learning case, as it emphasizes the combined role of diagnostic ancillary techniques along with clinical judgments for management. The case also makes us more vigilant towards the pathobiology of DLBCL and dynamics of personalized individual treatment response.